Evklidov algoritem - Jerman, Marjan (Matematika v šoli, 2013)
The article briefly describes the history of Euclidean algorithm. Described within are some classical methods of its use in the theory of numbers: Bézout's identity, solving linear Diophantine equations, its application on the Chinese remainder theorem, approximation of the roots of natural numbers with help of continued fractions, and solving Pell's equation. The article concludes with a generalization based on Euclidean domains, mentioning the domains of polynomials in one variable with coefficients from a division ring, Gaussian integers and Eisenstein integers.
Keywords: Bezoutova identiteta; Bézout's identity; Chinese remainder theorem; continued fractions; Euclidean algorithm; Euclidean domain; Evklidov algoritem; evklidski kolobar; history of mathematics; kitajski izrek o ostankih; linear Diophantine equations; linearne diofantske enačbe; Pellova enačba; Pell's equation; verižni ulomki; zgodovina matematike